2020
DOI: 10.22270/ujpr.v5i3.411
|View full text |Cite
|
Sign up to set email alerts
|

Urinary Tract Infections in Post Operative Patients: Prevalence Rate, Bacterial Profile, Antibiotic Sensitivity and Specific Risk Factors

Abstract: Background and objective: Urinary tract infections (UTIs) are the most common minor complication after operations, mostly due to bladder catheterization that used routinely during operations. This investigation seeks to determine prevalence rate, bacterial features, antibiotic sensitivity and risk factors for urinary tract infection in postoperative patients in tertiary hospitals in Sana’a, Yemen. Methods: This prospective analysis included 390 patients undergoing surgery between 2017 and 2018 at Al-Thaw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Recently, a study by Al-Hai et al [15] observed that the gram-negative bacteria recorded a high resistance to ampicillin, nalidixic acid, ceftriaxone, and cotrimoxazole. However, not enough information exists about the resistance of gramnegative bacteria to some common antibiotics in Sana'a city, Yemen.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, a study by Al-Hai et al [15] observed that the gram-negative bacteria recorded a high resistance to ampicillin, nalidixic acid, ceftriaxone, and cotrimoxazole. However, not enough information exists about the resistance of gramnegative bacteria to some common antibiotics in Sana'a city, Yemen.…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of antimicrobial-resistant bacteria in Yemen was documented by investigators [14][15][16][17]. It was found that P. aeruginosa and E. coli isolated from wound infection had a high resistance to tetracycline, erythromycin, nalidixic acid, and nitrofurantoin [4].…”
Section: Introductionmentioning
confidence: 99%